Cutaneous squamous cell carcinoma progression is associated with decreased GATA‐3 immunohistochemical staining. (10th February 2016) - Solus, Jason F.; Hassan, Khaled; Lee, Sena J.; Hsi, Andy C.; Rosman, Ilana S.; Dehmeri, Shadmehr; Schaffer, András
Abstract : Background: The GATA family of transcription factors is an essential regulator of cellular proliferation and differentiation. In the skin, GATA‐3 is critical for epidermal stratification and maintenance of barrier function. A role for GATA‐3 in the development of human cutaneous squamous cell carcinoma (SCC) is not known. Here, we investigated GATA‐3 immunohistochemical staining in premalignant and invasive cutaneous SCC from sun‐exposed and sun‐protected skin. Methods: GATA‐3 immunohistochemistry was performed on actinic keratoses (AK) (n = 19), in situ squamous cell carcinomas with actinic [SCCIS (A)] (n = 9) or bowenoid features [SCCIS (B)] (n = 17), well‐, moderately and poorly differentiated SCC (n = 36), Bowenoid papulosis of the perineum (n = 15) and penile SCC (pSCC) (n = 10). Results: We found that GATA‐3 immunohistochemical staining is progressively lost in sun‐exposed skin as neoplasia progresses from pre‐cancerous AK to SCCIS (A), and ultimately, to SCC, which shows near absent GATA‐3 staining. This reduction in GATA‐3 staining is independent of histological grade in SCC. Only slight down‐regulation of GATA‐3 was seen in all cases of SCCIS (B) and Bowenoid papulosis, while near absent GATA‐3 expression was seen in pSCC. Conclusion: We propose that decreased GATA‐3 immunohistochemical staining is associated with cutaneous SCC progression on both sun‐exposed and sun‐protected sites.